Research on the Effect of Welding Parameters on Tensile Properties Of Dissimilar Base Materials (Low Carbon Steel Aisi 1020 And Stainless Steel Aisi 304) Rotary Friction Welding Joint Using Taguchi Method - Dang, Thiện Ngôn; Tao , Anh Tuấn (Journal of Technical Education Science, 2018)
The following study objective is an investigation in order to determine welding parameter effect on dissimilar base materials (low carbon steel AISI 1020 and stainless steel AISI 304) rotary friction welding joint. In rotary friction welding process, the tensile strength is tested as welding joint quality. Friction time t1, friction force F2, rotary speed N which greatly affect the tensile strength is investigated by the Taguchi method. With the parameter setting: t1 = 6s, F2 = 100 MPa, N = 1450 rpm, upsetting length l =3 mm (selected) and workpiece diameter D = 20 mm. The results show that tensile strength can be from 86.89% to 93.68% AISI 1020 tensile strength. Within the experimental parameter range, welding force F2 and rotary (friction) speed N mainly impact on the tensile strength weld joint (78% and 28% respectively), and the effect of welding time t1 is not significant.